REGIONAL FINANCIAL MANAGEMENT AND INDEPENDENCE PROJECTION WITH THE ISSUANCE OF THE HKPD LAW - Akhmad Syarifudin; Rizki Ramadhani (Jurnal Ekonomi, 2023)
The achievements of fiscal decentralization over the past 20 years have shown positive performance, but the central fiscal synergy with the regions has not been optimal. The issuance of Law No.1/2022 concerning Central and Regional Financial Relations (HKPD) encourages creative and sustainable financing based on cooperation through the Funding Synergy scheme. This study aims to examine financial management and project Local Own Revenue (PAD) referring to the HKPD Law. Observation of statistical data using Regional Financial Reports and BPS. The least square method is used for forecasting and projection of PAD. The results of the analysis of district/city PAD during the Covid-19 period in 2020-2021 generally decreased, but PAD grew 5% exceeding the Balancing Fund which grew 2% during 2017-2021. The results of forecasting PAD nationally for 2024 referring to the HKPD Law show a positive trend with a steep slope so that the level of independence in general will increase in class, except for regions with a Regional Financial Independence Ratio (RKKD) of 0-18%; 25-38% and 50-63% estimated level of independence has not changed. The results of an empirical study in Kebumen, RKKD 21% (very low), decentralization 18% (poor category), effectiveness of PAD > 100% (effective), and local tax revenues and fees have a positive trend so that PAD will increase rapidly. To support the implementation of the HKPD Law, regional readiness is needed by encouraging the economy and investment, identifying tax options, extensifying the tax base, reducing administration and compliance costs and harmonization with other laws and regulations,